The Role of Female Judges: Gender Sensitivity and The Quality of Islamic Family Court Decisions - Syaiful Bakri (STAI Miftahul Ula Nganjuk, 2026)
This study aims to analyze the role of female judges in religious court practice, particularly in relation to gender sensitivity and the quality of rulings in Islamic family law cases. The study focuses on how the perspectives and social experiences of female judges contribute to the realization of substantive justice for the parties involved in litigation, especially women and children. The research method employed is normative legal research using a conceptual and socio-legal approach. Data were obtained through a literature review of legislation, the Compilation of Islamic Law, fiqh literature, and an analysis of relevant religious court rulings. The research results indicate that female judges possess significant potential to strengthen gender sensitivity in legal deliberations, although gender sensitivity is not solely determined by biological sex. The presence of female judges contributes to rulings that are more contextual, empathetic, and oriented toward the protection of vulnerable groups. Thus, strengthening the role of female judges and the gender perspective is a crucial factor in the transformation of Islamic family law toward greater justice.